Land Suitability Model for Curry - Atang Sutandi; Baba Barus (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
Agribusiness of herbal medicine is more important in the future due to raw material pharmaceutical industry tends to usematerials naturally produced To develop herbal medicine with high quality requires the criteria of land suitability based onyield quality, which is represented by active compounds. The compounds are resulted from secondary metabolite that isrelated to environmental conditions. The purpose of this study was to generate the land suitability criteria for curry withcurcuma production base. A total of 49 curry plantation sites were sampled for plant age, productivity, and landcharacteristics, as well as soil and rhizome samples for laboratory analysis. Age-adjusted curcuma production was used as the yield response, which were plotted against land characteristics. Boundary lines confining the resultant scatter of points were then mathematically described. The boundary lines defined curcuma yields that may occur under a given set ofconditions and could be used to determine land suitability criteria. The criteria were done by using projection of lineintersection between boundary line and yield cut off. Land characteristic and curcuma yield relationships had similar pattern, the scalier data were more skewness with higher yields and the scalier confined by boundary lines. By using the lines, every land characteristics that were studied, could be determine to establish land suitability criteria for curry, except for wateravailability and aluminum saturation.